2013
DOI: 10.1016/j.lwt.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Defatted kenaf seed meal (DKSM): Prospective edible flour from agricultural waste with high antioxidant activity

Abstract: a b s t r a c tThe present study reports nutritional composition, phenolic content and antioxidant activity of defatted kenaf seed meal (DKSM) in comparison to wheat, rice and sweet potato flours. Proximate analysis revealed that DKSM was high in protein (26.19 g/100 g DKSM) and carbohydrate (57.09 g/100 g DKSM). Magnesium, potassium and phosphorus were the major minerals (>1 g/100 g DKSM) found in DKSM through Energy Dispersive X-ray Spectrometric analysis. DKSM also exhibited appreciably higher total phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…ABTS• + scavenging activity was done according to the method by Chan et al [24]. In order to produce the ABTS radical cation (ABTS• + ), 50 ml of 7 mM ABTS stock solution was added to 50 ml of 2.45 mM potassium persulfate and kept at an ambient temperature for 24 h in the dark.…”
Section: Abts• + Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…ABTS• + scavenging activity was done according to the method by Chan et al [24]. In order to produce the ABTS radical cation (ABTS• + ), 50 ml of 7 mM ABTS stock solution was added to 50 ml of 2.45 mM potassium persulfate and kept at an ambient temperature for 24 h in the dark.…”
Section: Abts• + Scavenging Activitymentioning
confidence: 99%
“…The β-carotene bleaching inhibitory activity of tested fractions was evaluated by the linoleic model system described by Chan et al [24] with slight modifications. In brief, 6 ml of β-carotene solution (6 mg β-carotene in 10 ml chloroform) was added to 120 mg of linoleic acid and 1200 mg of Tween-20 followed by drying under a stream of nitrogen gas to fully remove the chloroform.…”
Section: β-Carotene Bleaching Assaymentioning
confidence: 99%
“…Research investigations showed the potential of kenaf seed derived value added nutritional foods like defatted kenaf seed meal (DKSM), protein concentrates from defatted kenaf seed, kenaf seed cake etc. which exhibit promising health promoting functions (Mariod et al, 2010(Mariod et al, , 2012Chan et al, 2013;Zawawi et al, 2014). A number of factors such as variety, location and environmental conditions affect the nutritional composition (amounts of protein, oil, carbohydrates and dietary fiber) of roselle seeds (Rao, 1996;Abu-Tarbouch et al, 1997;El-Adawy and and Khalil, 1994;Hainida et al, 2008a,b).…”
Section: Sr Nomentioning
confidence: 99%
“…Deficiency of antioxidants in living organisms leads to oxidative stress. The natural products rich in antioxidants are of great importance for scientists Chan, Khong, Iqbal, Mansor and Ismail, 2013;Craft, Kosinska, Amarowicz, & Pegg, 2010). Honey a sweet natural product produced by honey bees form nectar and other plant juices is also a good source of antioxidants.…”
Section: Introductionmentioning
confidence: 99%